2022
DOI: 10.3390/app12126003
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Novel Design for a Tubular Solid Oxide Fuel Cell Current Collector

Abstract: This study presents a novel current collector design for a tubular SOFC and numerically investigates its performance. The new current collector design has a flow channel with a trapezoidal shape. Several channels, such as four, eight, and twelve, are investigated, and their effects on cell performance are reported and compared. Additionally, a traditional tubular SOFC and the newly developed design are presented. The equations of mass conservation, momentum, charge transport, and energy were considered in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Current collectors are used to collect or deliver electrons to and from the cell electrodes. The current collectors should be porous enough over the active area of the cell to allow gas flow to the triple phase boundaries (TPB) (Ahmed and Ahmed, 2022). Performance data in the literature, such as area specific resistance (ASR) and power outputs, for fuel cells with similar compositions and fabrication processes may vary…”
Section: Current Collection Methodsmentioning
confidence: 99%
“…Current collectors are used to collect or deliver electrons to and from the cell electrodes. The current collectors should be porous enough over the active area of the cell to allow gas flow to the triple phase boundaries (TPB) (Ahmed and Ahmed, 2022). Performance data in the literature, such as area specific resistance (ASR) and power outputs, for fuel cells with similar compositions and fabrication processes may vary…”
Section: Current Collection Methodsmentioning
confidence: 99%
“…They found that the current density of the designed button-type O-SOFCs was improved significantly to about 108.5% at an average voltage of 0.6 V by operating the cell at a temperature of 1023 K, as well as the oxygen and hydrogen flow rates were maintained at 0.6 L min −1 and 1.8 L min −1 . In addition, it has been found that there are different structures (tubular, button-type) of SOFCs, which were designed and analyzed its behavior through CFD modeling and experimentally [60]. However, in PCFCs, only planar-type stacks were modeled and studied for behavior.…”
Section: Comparison Of Modeling Of Sofc With Pcfcmentioning
confidence: 99%
“…As a representative of electrochemical power generation equipment [1,2], the urgency of fuel cell technology needs and the uncertainty of global energy security are increasing. Scientists around the world are actively seeking clean energy that can achieve optimal conversion efficiency [3,4]. The solid oxide fuel cell (SOFC) has become an attractive option for electricity generation due to its efficient electrochemical power generation reaction and environmentally friendly characteristics, with water as the byproduct [5,6].…”
Section: Introductionmentioning
confidence: 99%